British Increasingly Hesitant on NATO Expansion. - United States Information Agency. Office of Research and Media Reaction.; Teare, Mark. (Tufts University. Tisch Library., 2019)
An underlying theme of British politics, pushed to the fore by the upcoming national elections, is how "European" Britain should be. The debate over British involvement in European integration could have an impact on security thinking. A USIA poll suggests the British public may be less inclined now to support security proposals that extend to all of Europe.; Opinion Analysis M-63-97